Then came you [videorecording (DVD)] - Trigiani, Adriana; Trigiani, Adriana; Ferguson, Craig 1962-; Gifford, Kathie Lee, 1953-; Gifford, Kathie Lee, 1953-; Gifford, Kathie Lee, 1953-; Kiernan, Ford (Lionsgate, 2020)
When a widow takes a trip around the world with her husband's ashes, she finds a new love interest on her first stop.